Assessment of agricultural information needs in African, Caribbean and Pacific (ACP) States for CTA’s Products and Services: Phase 1: Pacific: Country Report: Samoa - Tofinga, Mareko P. (Technical Centre for Agricultural and Rural Cooperation, 2004)
The work carried out in this report assessed the agricultural information needs in Samoa as part of a wider assessment of needs in Africa, Caribbean and Pacific (ACP) states.